Developmental Disabilities in Children: Medical and Social Challenges in Central India - Jain, Jenisha; Jain, Shikhar (National Journal of Community Medicine, 2017)
Background: There is paucity of facilities and social supports available for help of patients with developmental disabilities , especially in developing countries like India Aim: The present study was done to determine the profile of children presenting with developmental disabilities, social support available to their families and common problems encountered by them Materials and methods: This questionnaire based study was done by interviewing and examining consecutive patients with different developmental disabilities over a six month period at a tertiary level centre in western India Results: We noted that most of the cases were detected late, especially hearing impairment. Most parents faced depression and guilt on detection of such disabilities which improved later. Social and financial problems plagued most of the respondents. Most patients were nutritionally deprived Conclusion: The study highlights the problems in detection, treatment and social support to children with developmental disabilities and their families in Western Madhya Pradesh. There are gaps in the medical, educational and integration services for disabled children in our area and we need to make specific measures to address them.